2020
DOI: 10.1016/j.jnoncrysol.2020.119938
|View full text |Cite
|
Sign up to set email alerts
|

The opal-CT nanostructure

Abstract: Opal-CT, a silica polymorph in marine sedimentary siliceous rocks, exhibits commonly a form of spheres about ten micrometers in diameter ("lepispheres"). Quantitative infrared analyses were performed with a special attention to the band related to the Si-O-Si angle and to the [SiO 4 ] tetrahedral framework. Opal-CT includes about 40 % non-crystalline structures mixed with crystalline ones related to tridymite. Under TEM a single opal-CT lepisphere section exhibits a nanostructure constituted of a stacking of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Consistent spectra were seen for each opal type, with typical examples shown in Figure 4. The three bands (Table 3) correspond to those previously found in powder ATR [7] and other transmission mode studies [9,[20][21][22]25,26]. The differentiating features of peaks at approximately 550 cm −1 for opal-A and 620 cm −1 for opal-C are again seen.…”
Section: Transmission Spectrasupporting
confidence: 82%
See 2 more Smart Citations
“…Consistent spectra were seen for each opal type, with typical examples shown in Figure 4. The three bands (Table 3) correspond to those previously found in powder ATR [7] and other transmission mode studies [9,[20][21][22]25,26]. The differentiating features of peaks at approximately 550 cm −1 for opal-A and 620 cm −1 for opal-C are again seen.…”
Section: Transmission Spectrasupporting
confidence: 82%
“…The broad and largely featureless XRD patterns of opal-AG and opal-AN imply that the silica species are amorphous. The nature of opal-CT has been in debate for many years [8,9], with many researchers claiming the structured XRD patterns are a result of a combination of cristobalite-and tridymite-like forms of silica. In previous work [7], we showed that opal-CT exhibits a progressive change from a broader to a sharper XRD pattern structure coupled with more defined Raman spectra with delineated peaks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of carbonate‐siliceous facies represented by opoka, gaize and horizons of cherts is one of the most distinctive features of the Late Cretaceous epicontinental European Basin (Clayton, 1986; Jurkowska & Świerczewska‐Gładysz, 2020b; Jurkowska et al., 2019; Maliva et al., 1989; Pożaryska, 1952; Sujkowski, 1931). Silica occurs in the form of an authigenic (precipitated in situ) polymorph represented by opal‐CT (hydrated, paracrystalline form of silica with disordered structure‐opaline silica; Fröhlich, 2020; Jeans, 1978; Jurkowska & Świerczewska‐Gładysz, 2020a, 2020b; Pożaryska, 1952; Sujkowski, 1931). Opal‐CT is characterized by a disordered structure composed of interlayered α‐cristobalite and α‐trydymite stacking units (Flörke, 1955; Jones & Segnit, 1971).…”
Section: Geological Settingmentioning
confidence: 99%
“…Other variability, such as in the amount of molecular water [7,[10][11][12][13], trace elements [14][15][16][17][18][19][20][21][22] and the mixture of silanols (Q 3 site with one oxygen as a silanol [23][24][25] with the remainder bridged to other silicon atoms) with fully substituted (Q 4 site all Si-O-Si bridged) species leads to a consensus that opal is not a true mineral. Despite extensive research, the structures of opal-A and opal-CT remain unresolved [3,12,26,27]. Opal-C shows similarities to cristobalite [2].…”
Section: Introductionmentioning
confidence: 99%